Planning Results for High Tibial Osteotomies in Degenerative Varus Osteoarthritis Using Standing and Supine Whole Leg Radiographs. Issue 1 (30th November 2020) - Bockmann, Benjamin; Nebelung, Wolfgang; Boese, Christoph K; Schulte, Tobias L; Venjakob, Arne J
Abstract : Objective: In this study, we hypothesized that standing and supine X‐rays lead to different preoperative planning results. Methods: The present study included 168 pictures from 81 patients who were treated surgically with high tibial osteotomy (HTO) for varus deformity between January 2017 and February 2018. Each patient underwent whole leg X‐ray examinations in both standing and supine position. On both images, the following parameters were measured: degree of axis deviation (DAD), mechanical lateral distal femoral angle (mLDFA), mechanical medial proximal tibial angle (mMPTA), width of medial (MJS) and lateral joint space (LJS), and the correction angle (CA). The results were correlated with the patients' age and body mass index (BMI). To analyze intra‐observer reliability, the same researcher, blinded to the previous measurements, remeasured all X‐rays from 10 patients 8 weeks after the initial measurements were carried out. Results: While mLDFA ( P = 0.075), mMPTA ( P = 0.435), and MJS ( P = 0.119) did not show any differences between the two modalities, LJS ( P = 0.016) and DAD ( P < 0.001) differed significantly, leading to different correction angles ( P < 0.001). The mean difference of the CA was 1.7° ± 2.2° (range, −2.6° to−15.4°). In 14 legs (17%), the standing X‐ray led to a correction angle that was at least 3° larger than the calculation revealed in the supine X‐ray; in 4 legs (5%), it was at least 5° larger. Increased BMI ( r = 0.191, P = 0.088) and older age ( r = 0.057, P = 0.605) did not show relevant correlation with DAD differences. However, more severe varus malalignment in the supine radiograph did correlate moderately with differences of correction angles between supine and weight‐bearing radiographs ( r = 0.414, P < 0.001). The analysis of the intra‐rater reliability revealed mediocre to excellent intercorrelation coefficients between the measurements of the observer. Conclusion: The use of supine and standing X‐ray images leads to different planning results when performing high tibial osteotomies for varus gonarthrosis. To avoid potential overcorrection, surgeons might consider increased lateral joint spaces on standing radiographs in osteoarthritic knees with varus deviation. Abstract : In this study, we hypothesized that standing and supine X‐rays lead to different preoperative planning results in high tibial osteotomies. Indeed, we did find an influence of the imaging modality on planning results; however, these results were not influenced by body mass and age.